Unveiling the silent struggle: navigating the labyrinth of mental health for parents of children with life-threatening illnesses in Pakistan - Faisal, Seyreen; Kamran, Tafiya Erum; Romaan Faisal (Journal of the Pakistan Medical Association, 2024)
Dear Editor, We write this letter to highlight the scarcely recognised complexity associated with the unrecognised mental health needs of parents of children diagnosed with life-threatening or life-limiting illnesses. It has been widely established that parents of children with disabilities are at an increased risk of developing variants of mental diseases when compared to parents of children without such disabilities. Parents tend to alter their lives socially to acclimatize themselves as caregivers for their children, therefore adopting a role that becomes far more labyrinthine as both parent and caregiver. (1) Mental health in general, is a subject that is insufficiently addressed in societal and scholarly contexts, specifically in Pakistan, particularly among parents. Within the scope of parents acting as sole caregivers, stress is a prominent determinant contributing to their mental health. Stress can attenuate parents’ and children’s abilities to navigate these circumstances and diminish their capacity for problem-solving and coping. (2) There are a myriad of factors that contribute to the reported prevalence of mental health-related disorders among parents of children with disabilities. Mental health remains a stigmatised entity. Such disregard impedes the delivery of healthcare towards patients suffering from mental health illnesses. There is a noteworthy hindrance in individuals facing such factors when amalgamatinge into society. When considering parental figures of diseased children, this facet serves to isolate further and reinforce such mental health illnesses. The lack of quantifiable data on anti-stigma interventions in Low and Middle-Income Countries, including Pakistan, underscores the urgent need for research. (3) Parents of children admitted to the ICU have a near-pervasive struggle with mental health and an innate inability to disclose their requirements for support. Factors barricading such disclosure should be identified and broken down through interventions, facilitating access to vital mental health support. (4) Caregivers must establish coping strategies, and remain a steady pillar of support and comfort to their child. The Keeping Hope Alive Toolkit intervention was established, which worked on fostering emotional experiences, living in the moment, remembering self and supporting social preferences, this intervention provided a template for emotional support. (5) We hope this letter can underscore how important supporting parental disclosure of unmet mental health needs is – a rampant and insufficiently reported plight in Pakistan. The ability to recognise these emotions and rectify them is not highlighted in this region but is imperative to implement, to improve the provision of healthcare to diseased children and their parents alike.